Transcendent Space, Reactionary-Modernism and the "Diabolic" Sublime: Walter Christaller, Edgar Kant, and Geography's Origins as a Modern Spatial Science. Issue 1 (2nd January 2018) - Olwig, Kenneth R.
Abstract : To show how the reactionary and modern were linked in the genesis of geography as a modern spatial science, this article traces the ideas and practice of two of the twentieth-century founders of spatial science, Walter Christaller and Edgar Kant, back to the origins of modernity in the Renaissance, when the "duplicitous" and "diabolic" cartographic space of the scenic landscape was constructed. Through this reexamination of the history of geography it is argued that Christaller's Nazism and Kant's "anthropo-ecological" theories must be understood against the cartographic background of a nationalization of space that created a problematic situation for the Eastern European German diaspora, with its medieval and Enlightenment era origins, and that continues to create conflicts for other diasporic minorities in other parts of the world where nationalism is still on the march. This study also reexamines the concepts of geographical determinism, possibilism and Lebensraum.